Vapour-Liquid Equilibrium for Systems Containing Ionic Liquids - A Review - Xiao, Ying; Bai, Peng; Jiang, Zhankun (Asian Journal of Chemistry, 2012)
Ionic liquids are a class of liquid state chemicals at room temperature, which have been proven to be promising solvent or entrainer in separation processes like extraction and extractive distillation, etc. Recent measurements reported on vapour-liquid equilibrium data are reviewed in this work. A brief summary about the screening is also displayed. Comparing the existing vapour-liquid equilibrium data and results, some suggestions are put forward to offer a reference for further development of ionic liquids.